Association of exposure to polycyclic aromatic hydrocarbons (estimated from job category) with concentration of 1-hydroxypyrene glucuronide in urine from workers at a steel plant. Issue 9 (September 1995) - Kang, D; Rothman, N; Cho, S H; Lim, H S; Kwon, H J; Kim, S M; Schwartz, B; Strickland, P T
Abstract : OBJECTIVES--Increased risk of lung cancer has been associated with employment in the steel industry. This association is thought to be due in part to increased concentrations of polycyclic aromatic hydrocarbons (PAHs) in air found in this work environment. Measurement of PAH metabolites in human urine provides a means of assessing individual internal dose of PAHs. This study examined the relative contribution of occupation and smoking to urinary concentration of 1-hydroxypyrene glucuronide (1-OHPG) among a group of workers at a steel plant. METHODS--Concentrations of 1-OHPG in urine from 44 workers with jobs associated with increased air concentrations of PAHs and 40 workers with jobs with low or no exposure to PAHs were measured. 20 workers in each group were not current smokers. Urinary 1-OHPG was measured by synchronous fluorescence spectroscopy after immunoaffinity chromatography specific for PAH metabolites. RESULTS--Mean (SEM) urinary 1-OHPG concentration was 2.16 (0.42) pmol/ml urine among the 44 occupationally exposed workers compared with 0.38 (0.05) among the 40 workers with no or low exposure (P < 0.0001). Mean urinary 1-OHPG concentration was 1.82 (0.41) pmol/ml urine among the 44 current smokers compared with 0.75 (0.20) among the 40 non-smokers (P < 0.005). Mean 1-OHPG concentrations in non-smokers were 0.26 (n = 20), 0.70 (n = 15), and 2.84 pmol/ml urine (n = 5) for strata of exposure to PAHs (no or low, mid, and high) based on job category; the corresponding values in smokers were 0.55 (n = 20), 0.94 (n = 12), and 4.91 pmol/ml (n = 12), respectively. Multiple linear regression showed significant differences between subjects in different PAH exposure with increased concentrations of 1-OHPG in urine. Amounts of foods containing PAHs ingested by this group of workers were relatively low and did not contribute significantly to urinary 1-OHPG concentrations. CONCLUSIONS--These results indicate that 1-OHPG is a common urinary metabolite in people with recent occupational exposure to PAHs and is associated with both job category and estimated stratum of PAH exposure.